Получение углеводородов топливного ряда из растительного масла - Кокорина Ю. С. Юлия Станиславовна; Богданов И. А. Илья Александрович; Алтынов А. А. Андрей Андреевич; Соснина Д. В. Дарья Вячеславовна (2023, 2023)
Текстовый файл